Front Cover: MALDI‐Imaging for Classification of Epithelial Ovarian Cancer Histotypes from a Tissue Microarray Using Machine Learning Methods. Issue 1 (7th February 2019) - Klein, Oliver; Kanter, Frederic; Kulbe, Hagen; Jank, Paul; Denkert, Carsten; Nebrich, Grit; Schmitt, Wolfgang D.; Wu, Zhiyang; Kunze, Catarina A.; Sehouli, Jalid; Darb‐Esfahani, Silvia; Braicu, Ioana; et al.
Abstract : Precise histological classification of epithelial ovarian cancer (EOC) subtypes is important for personalized treatment. The image, designed by Maria Hänel, illustrates the potential of imaging mass spectrometry combined with machine learning methods to explore spatial proteomic levels, enabling the classification of EOC histological subtypes. Applications include the development of new prognostic parameters in the tissue assessment of EOC. This is reported by Oliver Klein, Frederic Kanter, Hagen Kulbe, Paul Jank, Carsten Denkert, Grit Nebrich, Wolfgang D. Schmitt, Zhiyang Wu, Catarina A. Kunze, Jalid Sehouli, Silvia Darb‐Esfahani, Ioana Braicu, Jan Lellmann, Herbert Thiele, Eliane T. Taube in article1700181 .